A method validation for assay of imipramine hydrochloride in imipress tablet 25 mg by using high performance liquid chromatography/ photo diode array / Radiatul Nadiah Binti Razali - Razali, Radiatul Nadiah (2014)

(untitled)
Imipress Tablet 25 mg is one of the products of Chemical Company of Malaysia, Duopharma Sdn. Bhd, CCMD. The Active Pharmaceutical Ingredient is Imipramine Hydrochloride which contains 25 mg per tablet. Method validation was carried out in terms of specificity (force degradation), placebo analysis, linearity and range, accuracy, precision (repeatability and intermediate precision), robustness and solution stability. This method has been shown to be linear, accurate, precise, rugged and robust. The HPLC method is suitable for use as a stability indicating method for determination of Imipramine Hydrochloride content in Imipress Tablet 2 mg. Good linearity was established with R2 of 1.000 with the mean accuracy of 99.83%. All the RSD (%) were less than 2% and 1% for %RSD of standard peak area and %RSD of retention time, respectively. The analytical method developed and validated for assay by HPLC is suitable for the accurate and precise determination of Imipramine Hydrochloride content in Imipress Tablet 2 mg.